Pengaruh Kompensasi dan Pengembangan Karir Terhadap Produktivitas Karyawan Pada Coffee Comunitas Tenggarong - Okasari, Bela Putri; Askiah, Askiah; Hadiyanti, Sofia Ulfa Eka (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the influence of compensation and career development on employee productivity at Coffé Comunitas Tenggarong. Employing a quantitative approach with a survey method, data were collected from 30 employees using a Likert-scale questionnaire. Multiple linear regression analysis revealed that compensation (B = 0.078, sig = 0.001) and career development (B = 0.803, sig = 0.000) have a positive and significant impact on employee productivity, with career development exerting a stronger effect. The coefficient of determination (R² = 0.966) indicates that 96.6% of the variation in productivity is explained by these variables. Validity, reliability, and classical assumption tests (normality and homoscedasticity) were met, ensuring a robust regression model. These findings underscore the importance of competitive compensation and training programs in enhancing work efficiency in local cafes. The implication is that managers should strengthen career development strategies to support business sustainability.
Keywords: Compensation; Career Development; Employee Productivity